Informal Debt and Well-Being Among Small Business Entrepreneurs - Droller, F (Emerald Publishing, 2025)
Purpose Access to bank loans is often limited for small businesses in emerging economies, particularly during crises when capital becomes scarce. In such situations, financially underserved entrepreneurs may resort to unregulated financing options, often involving high-interest, illegal loans. This study aims to examine the relationship between informal, unregulated debt, financial education and well-being among entrepreneurs in Chile. Design/methodology/approach The empirical analysis is based on a novel large data set from the Impact of the COVID-19 pandemic on small businesses survey. The data set contains information on 1,191 entrepreneurs enrolled in Chile’s Small Business Development Center program. Linear probability and instrumental variable models are used to analyze the data. Findings Entrepreneurs with unregulated debt from moneylenders are more likely to have worse levels of mental well-being across multiple measures. Those who perceive a need for financial education are more likely to depend on informal, high-cost financing. Financial-advisory assistance reduces the probability of relying on unregulated debt. Practical implications This study highlights the role of access to financial education and formal sources of capital in improving the well-being of entrepreneurs. Moreover, this study underscores the negative consequences of illegal lending practices often associated with organized crime, which target entrepreneurs with limited financing options. Originality/value This research provides new insights into the adverse effects of informal, unregulated lending on well-being. It emphasizes how financial education can alleviate financial strain and improve mental health outcomes among small business owners. © 2025 Emerald Publishing Limited